(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
From the first quarter of the 19th century, there is information about the "mysterious" writings found in Siberia and Mongolia. But these writings remained unread and "mysterious" for a long time. In 1889, Finnish scientists found them on the Enasoy River compiled an atlas of monuments. Because Finnish scientists believed that these writings related to the past of the Finnish people until they were read. These texts were first read by the Danish scientist Wilhelm Thomsen in 1893. Based on his discovery, the Russian scientist V.V. Radlov had the honor of being published.